THE HEMOSTASYS IN NEUROSURGERY (literature review) (Medical science of Uzbekistan, 2023)
The problem of intraoperative hemostasis has been studied for a very long time, but remains relevant due to the many shortcomings of the proposed methods for stopping bleeding. In this article, we have uncovered the different types of hemostatics and dwelled in detail on the advantages and disadvantages of each of them.